Automatic Generation of Navigable User Interfaces and Executable Logic from Customer Requirements - Kuttan Pillai, Harikrishnan (Digital Repository of Theses, 2025)
This research analyzes the current state of the art in this field and aims to propose a new system for automatically converting the user requirements to end-user applications. The system translates the stated user requirements into an intermediate language after they have been gathered, and with the aid of pre-trained data, it can then translate them into UI code. In this phase, both business logic and navigation logic are integrated. We also apply an iterative model variant in the proposed research, where code is generated based on continuous feedback from various iterations of customer requirement gatherings. Keywords: automation, artificial intelligence, software engineering, natural language processing.